2010
DOI: 10.4103/0972-124x.75914
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal alveolar bone loss: A periodontal orphan

Abstract: Background:Attempts to successfully regenerate lost alveolar bone have always been a clinician’s dream. Angular defects, at least, have a fairer chance, but the same cannot be said about horizontal bone loss. The purpose of the present study was to evaluate the prevalence of horizontal alveolar bone loss and vertical bone defects in periodontal patients; and later, to correlate it with the treatment modalities available in the literature for horizontal and vertical bone defects.Materials and Methods:The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 18 publications
0
28
0
1
Order By: Relevance
“…These measurements are inferior to surgical measurements of alveolar bone height and clinical attachment measurements because they underestimate the extent of periodontitis compared with other methods (28). Accordingly, the extent of periodontitis in this study was underestimated (6,29). The sum of the maximum distances from the selected incisal points to the alveolar crest at 10 representative locations for visualizing the horizontal bony defect in the upper and lower jaw (30) and the sum of the bone heights at these locations were significantly correlated with the extent of the atherosclerotic burden.…”
Section: Discussionmentioning
confidence: 64%
“…These measurements are inferior to surgical measurements of alveolar bone height and clinical attachment measurements because they underestimate the extent of periodontitis compared with other methods (28). Accordingly, the extent of periodontitis in this study was underestimated (6,29). The sum of the maximum distances from the selected incisal points to the alveolar crest at 10 representative locations for visualizing the horizontal bony defect in the upper and lower jaw (30) and the sum of the bone heights at these locations were significantly correlated with the extent of the atherosclerotic burden.…”
Section: Discussionmentioning
confidence: 64%
“…In this regard, it should be noted that horizontal alveolar bone loss is a problem that periodontists often face; in fact, in a radiographic study, Jayakumar et al 31 reported that horizontal bone loss represents 92% of the total bone loss from periodontal patients. Conversely, the prevalence of intrabony defects has been shown to be significantly lower, ranging from 8% to 30.2% 32‐34 …”
Section: Discussionmentioning
confidence: 99%
“…Chronic periodontal disease has been reported to cause structural changes in normal alveolar bone, which results in different forms and varying degrees of alveolar bone defect seen in different parts of the same tooth. In our study, we analyzed the effect of root concavities on defects seen in the first premolar interproximal bone using CBCT scanning.…”
Section: Discussionmentioning
confidence: 99%